Artists unframed - Foresta, Merry A. (Princeton Architectural Press, 2015)
Artists unframed' features more than 100 images of artists at work and play. These images from the golden age of snapshot photography reveal unguarded (and sometimes unbuttoned) moments in the personal lives of artists who include Alexander Calder, Andy Warhol with John Lennon and Yoko Ono, Dizzy Gillespie, Jasper Johns, Frida Kahlo and Diego Rivera, Marcel Duchamp, Robert Motherwell, Pablo Picasso, E. M. Forster, Jackson Pollock and Lee Krasner, Eero Saarinen, and John Waters. The collection was exhibited at the Smithsonian in 2011, and there are plans to travel the show
9781616892951
Keywords: Ausstellungskatalog; Biografie; Artists / United States / Pictorial works / Exhibitions; Photography / United States / Exhibitions; Schnappschuss; Künstler; Fotografie